Revitalisasi Kelembagaan Dan Daya Tarik Wisata Curug Lawe Benowo Sebagai Upaya Pemberdayaan Ekonomi Masyarakat Desa Kalisidi Berbasis Digital Ecotourism - Nurdian Susilowati; Lesa Paranti; Fauzul Adzim; Siti Fatimah (Jurnal Bina Desa, 2026)
Lawe Benowo Waterfall is a natural tourist destination located in Kalisidi Village, West Ungaran District, Semarang Regency. This waterfall has captivating natural beauty. The purpose of this community service activity is to strengthen management capabilities through tourism management education and public speaking. The approach used is Participatory Rural Appraisal (PRA), implemented through counseling, mentoring, and training. The target community is the administrators and members of the Katuranga Tourism Group (Pokdarwis) of Kalisidi Village, totaling 20 people. The results of this activity include institutional strengthening, increased management capacity, and the expansion of digital ecotourism-based tourism promotion, which contribute to increased community income. Pokdarwis Katuranga can communicate in English and French. During the training and language practice sessions, participants showed great enthusiasm. This community service activity successfully introduced an innovation in ecotourism-based tourism management to create sustainable ecotourism at Lawe Benowo Waterfall.